Angel on one shoulder: Can perceived organizational support moderate the relationship between the Dark Triad traits and counterproductive work behavior?. (1st May 2017) - Palmer, Joshua C.; Komarraju, Meera; Carter, Min Z.; Karau, Steven J.
Abstract: Drawing on social exchange theory and a person-situation framework, we examined perceived organizational support as a moderator of the relationship between the Dark Triad personality traits of narcissism, Machiavellianism, and psychopathy with specific types of counterproductive work behavior (i.e., sabotage, production deviance, withdrawal, theft, and abuse). Using a sample of 208 currently-employed online participants and structural equation modeling analyses we found that individuals scoring high on the Dark Triad traits reported engaging in some types of counterproductive work behavior less frequently when they perceived higher levels of organizational support. Our results support the person-situation interactionist model and suggest that individuals possessing higher levels of narcissism and psychopathy engage in certain types of counterproductive work behavior relatively less frequently when they perceive the organization as being supportive. Highlights: Counterproductive work behaviors (CWB) are intentional harmful workplace behavior. Employees high in the Dark Triad traits reported higher levels of CWB. Perceived organizational support (POS) occurs when an employee feels appreciated. POS moderated the Dark Triad traits-CWB relationship for some types of CWB. POS may reduce some types of CWB for employees high in the Dark Triad traits.